Royalties do petróleo no conflito territorial entre os municípios sergipanos de Pacatuba e Pirambu - Camargos, Tássia Henriques de Morais (2017)
Exploiting natural oil and gas in Sergipe, from the second half of the twentieth century onwards, together with other mineral resources, enhanced the local economy by introducing the mineral extractive industry, contributing to the transformation of a traditionally agricultural economy state into one of the biggest oil producing state of Brazil. In that context, this study looks into this theme and into the territorial dispute between Sergipe’s municipalties Pacatuba and Pirambu. So, the conflict was analysed, debating its causes and consequences to the involved population and keeping the social rights thereof. To that and other specific goals, distinct methodological procedures associated to different stages were used, namely: searching bibliographical and documental data of various times, analysing court papers and visiting the municipalities, in order to interact with the disputed area people. Results show that such territorial conflict began in 2002, soon after the installation of the Robalo Oil Collecting Plant, by Petrobras, in geographical areas always known to be Pacatuba’s. Some time before that, IBGE (Brazilian Geography and Statistics Institute), on making the 2000 Statistic Municipal Map, aiming only populational counting, altered the boundaries of the two municipalities, affecting the distribution of oil royalties, and thereby harming especially the municipality of Pacatuba. Furthemore, the conflict, as time went on, influenced local political issues, impacting mainly the mineral extracting activity, damaging the citizens quality of life. So, taking into consideration the intentions in the municipal arena, and the role of the interested ones, one can see a paradox between a potentally rich subsoil and the growing poverty of the population, to which part of the rights and guarantees of constitutional article sixth do not exist.